An Improved Immersed Boundary Method with New Forcing Point Searching Scheme for Simulation of Bodies in Free Surface Flows (Communications in Computational Physics, 2018)
An improved immersed boundary method is proposed and applied to simulatefluid-structure interactions by combining a level set method for free water surfacecapturing. An efficient Navier-Stokes equation solver adopting the fractional stepmethod at a staggered Cartesian grid system is used to solve the incompressible fluidmotion. A new efficient algorithm to search forcing points near the immersed bodyboundary is developed. The searching schemes for forcing points located both insideand outside the solid phase with the linear interpolation schemes for the determinationof velocities at forcing points are presented and compared via the case of dam breakover obstacles. The accuracy and effectiveness of the proposed forcing point searchingschemes are further demonstrated by the study of wave propagation over a submergedbar and more challenging cases of wedge with prescribed velocity or falling freely intothe water. By the extensive comparison of present numerical results with other experimentaland numerical data, it suggests that the present improved immersed boundarymethod with the new forcing point searching scheme has a better performance and isvery promising due to its accuracy, efficiency and ease of implementation. Furthermore,the present numerical results show that the outside forcing scheme is superiorover the inside forcing scheme.